Tapeworms of freshwater fishes in North America: an integrative review of taxonomy, phylogeny, host specificity, and research priorities - Scholz, Tomáš; Kuchta, Roman (Frontiers in Veterinary Science, 2025)
Tapeworms (Cestoda) are a diverse group of parasitic flatworms that are highly specialized in a parasitic lifestyle. The freshwater fish tapeworms of North America have been relatively well studied since 1855, although their diversity is limited compared to other regions. Most knowledge was gained in the 20th century, with research declining in recent decades, although some groups have recently been revised based on morphological and molecular data. This review updates the current understanding of species diversity, phylogenetic relationships and host–parasite interactions based on a critical re-evaluation of the earlier records. The new data can also inform fisheries management, invasive species control and public health surveillance. Currently, 130 valid adult species are known in six orders, most of which are native to the Nearctic, with the USA having the greatest diversity (121 species). The vast majority of North American fish tapeworms exhibit narrow host specificity, with almost three quarters specializing in a single host species or host genus. Larval stages (metacestodes) from four orders also occur in fish, but are difficult to identify morphologically. Future work should focus primarily on little-studied fish groups and regions with probably undescribed diversity (e.g., the southern USA), combined with integrative taxonomic approaches.